VALIDITAS MEDIA DIORAMA BERBASIS AUGMENTED REALITY MATERI PERUBAHAN WUJUD BENDA KELAS IV SD - Damanik, Bella Silvesteria; Sastrawati, Eka; Risdalina, Risdalina (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to describe the validity level of Augmented Reality (AR)-based diorama media in teaching and learning Science and Mathematics subject on the material of Changes in the Form of Objects for fourth-grade elementary school students. The study used a Research and Development (R&D) approach with the ADDIE development model, which was limited to the development stage because the focus of the study was on assessing product feasibility through expert validation, without continuing to small or large group trials. The analysis stage was conducted to identify learning needs, which showed that students needed concrete and interactive media to better understand the process of changes in form. The design stage produced an A4-sized diorama design divided into four concept spaces (condensation, evaporation, freezing, and melting), complete with material layout, usage instructions, and scanning markers. The visual design of the diorama was created using Canva, while the AR content was developed through Assemblr Edu to display interactive objects/animations when scanned using a device. The development stage realized the design into a complete product, accompanied by functional testing to ensure that the markers and AR visuals appeared stably before validation. Validation results showed a 93.33% success rate for content, 100% for language, and 92% for media. Based on these results, AR-based diorama media is considered highly suitable for use as an alternative learning medium for IPAS material on changes in the form of objects in elementary schools, and has the potential to increase interest in learning and strengthen conceptual understanding through concrete and interactive visualization. ABSTRAKPenelitian ini bertujuan mendeskripsikan tingkat validitas media diorama berbasis Augmented Reality (AR) pada pembelajaran IPAS materi Perubahan Wujud Benda untuk siswa kelas IV Sekolah Dasar. Penelitian menggunakan pendekatan Research and Development (R&D) dengan model pengembangan ADDIE, yang dibatasi sampai tahap development karena fokus penelitian berada pada penilaian kelayakan produk melalui validasi ahli, tanpa dilanjutkan pada uji coba kelompok kecil maupun kelompok besar. Tahap analysis dilakukan untuk mengidentifikasi kebutuhan pembelajaran, yang menunjukkan bahwa siswa memerlukan media konkret dan interaktif agar lebih mudah memahami proses perubahan wujud. Tahap design menghasilkan rancangan diorama ukuran A4 yang dibagi menjadi empat ruang konsep (mengembun, menguap, membeku, dan mencair), lengkap dengan tata letak materi, petunjuk penggunaan, serta penanda pemindaian. Desain visual diorama disusun menggunakan Canva, sedangkan konten AR dikembangkan melalui Assemblr Edu untuk menampilkan objek interaktif saat dipindai menggunakan gawai. Tahap development merealisasikan rancangan menjadi produk utuh, disertai uji fungsional untuk memastikan keterhubungan penanda dan kemunculan visual AR berjalan stabil sebelum dilakukan validasi. Hasil validasi menunjukkan persentase 93,33% pada aspek materi, 100% pada aspek bahasa, dan 92% pada aspek media. Berdasarkan hasil tersebut, media diorama berbasis AR dinyatakan sangat layak digunakan sebagai alternatif media pembelajaran IPAS materi perubahan wujud benda di sekolah dasar, serta berpotensi meningkatkan ketertarikan belajar dan memperkuat pemahaman konsep melalui visualisasi yang konkret dan interaktif.